A fast Li-ion conducting Li7.1La3Sr0.05Zr1.95O12 embedded electrospun PVDF-HFP nanohybrid membrane electrolyte for all-solid-state Li-ion capacitors. (December 2020) - Maurya, Dheeraj K.; Balan, Balakrishnan; Murugadoss, Vignesh; Yan, Chao; Angaiah, Subramania
Graphical abstract: Highlights: Li7.1 La3 Sr0.05 Zr1.95 O12 embedded electrospun PVDF-HFP polymer membrane based all solid-state electrolyte is prepared. 15 wt.% of LLSZO containing esHPM- shows an enhanced electrolyte uptake, porosity and thermal stability. 15 wt.% of LLSZO containing esHPME exhibits an excellent ionic conductivity of 2.94 × 10 −3 Scm -1 and voltage window of 4.5 V. LiCoO2 /esHPME (15 wt.% of LLSZO)/AC delivers a specific capacitance of 68.75 F g −1 at the current density of 1 Ag −1 . Abstract: Hybrid polymer electrolytes with high dimensional stability and low electrode/electrolyte interfacial resistance have drawn exceptional attention as an electrolyte for all-solid-state Li-ion capacitors. Herein, various weight percentages of Li7.1 La3 Sr0.05 Zr1.95 O12 (LLSZO) embedded electrospun PVdF-HFP/LiPF6 based nanohybrid polymer membrane electrolytes (esHPME) are prepared for Li-ion capacitors. Li7.1 La3 Sr0.05 Zr1.95 O12 (LLSZO) garnet is prepared by a simple wet combustion technique and its structure and phase purity is confirmed by XRD studies. The surface morphology is investigated by FE-SEM studies. The thermal stability test reveals that the addition of LLSZO in the electrospun PVdF-HFP nanohybrid membrane significantly improves its thermal stability. 15 wt.% of LLSZO/PVdF-HFP/LiPF6 nanohybrid membrane electrolyte exhibits the ionic conductivity of 2.94 × 10 −3 Scm -1, which is higher than that of other wt.% of LLSZO embedded PVdF-HFP/LiPF6 nanohybrid membrane electrolytes. Its electrochemical potential window is found to be 4.5 V. A LiCoO2 / esHPME (15 wt.% of LLSZO)/AC based Li-ion capacitor is assembled and its specific capacitance is found to be 68.75 Fg -1 at the current density of 1 Ag -1 with ∼80 % of its initial capacitance even after 1000 cycles of charging-discharging. These results reveal that 15 wt.% of LLSZO/PVdF-HFP/LiPF6 based nanohybrid membrane electrolyte can be used as a potential candidate to develop high performance all-solid-state flexible Li-ion capacitor.